HPV Awareness and Willingness to HPV Vaccination among High-Risk Men attending an STI Clinic in Puerto Rico - Colón-López, Vivian; Del Toro-Mejías, Lizbeth M.; Ortiz, Ana P.; Tortolero-Luna, Guillermo; Palefsky, Joel M. (Puerto Rico Health Sciences Journal, 2012)
Objective: An HPV vaccine has been approved for men aged 9 to 26 in the US for the prevention of genital warts and anal cancer. The purpose of this study is to describe 1) HPV vaccine awareness, 2) willingness to get the HPV vaccine and 3) perceived susceptibility to HPV-related cancers and genital warts among men 18-26 years old who attend an STI clinic in San Juan, Puerto Rico (PR). Methods: A cross-sectional pilot study consisting of 206 HIV+/HIV- men. For purpose of this analysis, only those participants aged ≤26 years old were included in this analysis (n=46). Results: None of the study participants had been vaccinated against HPV. Fewer than a third knew about the HPV vaccine (28.3%). However, more than half (76.9%) were willing to be vaccinated against HPV. Information sources about the HPV vaccine included their female sexual partners (13.0%), a female sexual partner who received the vaccine (8.7%) and a male sexual partner (2.2%). Most participants reported that the main reason that would increase their willingness to get vaccinated was if a physician recommend the vaccine (95.7%). Perceived susceptibility was low, particularly for anal and oral cancer. Conclusion: This pilot study shows poor awareness of the HPV vaccine, although willingness to getting the HPV vaccine was high among those who knew about the vaccine. Future studies should try to evaluate this paradox and study in depth willingness and barriers to vaccination among male sub-groups, such as men who have sex with men (MSM). These studies should also evaluate predictors of uptake of the HPV vaccine among men in this and other STI clinics in PR, in order to develop interventions to increase male vaccination.